Community-engaged curricula in higher education: The case of a master’s programme in Play Therapy - Wilson, Lizane; Bitzer, Eli; Newmark, Rona (South African Journal of Higher Education, 2016)
This article presents the results from research on community-engaged curricula using feedback from international and South African academics who teach on postgraduate programmes with a community engagement component. It also includes findings from a sample programme at a South African university. Findings suggest that at least five important issues are related to community-engaged Play Therapy master’s programmes: Programme relevance, integrated scholarship, community-based research, reciprocal learning and close academic staff involvement. Based on these findings a curriculum framework is suggested which caters for an integrated scholarship approach in Play Therapy master’s programmes that closely engage with community needs. Such a framework may relate to similar or other professional master’s programme curricula.